(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2022)
The Chittagong Hill Tracts (CHT) is situated in the Southeastern Bangladesh having an area of 13,295 km2. Bandarban is one of the hill districts of CHT with diverse natural resources and ethnic communities. This paper is based on the review of published papers, reports, books related to Bandarban district of CHT giving emphasis on the landscape, natural resources, and the indigenous peoples in the CHT. The available information is synthesized to understand the overall state of natural resources degradation with special focus on land, soil, forest, fisheries, and livestock, etc. The traditional agricultural system of jhum cultivation is not sustainable due to population pressure, reduction of fallow period and soil degradation. The paper also presented the major causes of resource destruction along with the opportunities and challenges to the existing natural resource management in Bandarban. The prolonged conflict of land tenure and settlement of plain land people needs to be addressed at priority basis for the betterment of the hill people. J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(2): 84-94